2016
DOI: 10.1111/jace.14609
|View full text |Cite
|
Sign up to set email alerts
|

Computation of sintering stress and bulk viscosity from microtomographic images in viscous sintering of glass particles

Abstract: Sintering stress and bulk viscosity were derived as functions of relative density from microtomographic images in viscous sintering of glass particles. Three methods were proposed to estimate the sintering stress from relative density, specific surface area, and average of curvature on pore surface, which were directly measured by X‐ray microtomography. The surface energy method gave valid value in the final stage of sintering, while the mixed method gave better estimation in the intermediate stage. For the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The macroscopic quantities such as sintering stress 21 23 and bulk viscosity 20 , 24 can be determined rigorously for some idealized microstructures in equilibrium. However, for real porous structures which are nonequilibrium, non-periodic, and nonuniform, it is still a challenge to estimate macroscopic quantities from microstructures observed by X-ray microtomography 25 27 . It is recognized that the most appropriate method for determining sintering stress should be selected depending on sintering stage 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic quantities such as sintering stress 21 23 and bulk viscosity 20 , 24 can be determined rigorously for some idealized microstructures in equilibrium. However, for real porous structures which are nonequilibrium, non-periodic, and nonuniform, it is still a challenge to estimate macroscopic quantities from microstructures observed by X-ray microtomography 25 27 . It is recognized that the most appropriate method for determining sintering stress should be selected depending on sintering stage 27 .…”
Section: Introductionmentioning
confidence: 99%
“…By employing a simple first‐order iterative procedure, the derived formula can be a valuable extension of the continuum theory of sintering. Wakai et al have analyzed the sintering force of two sphere particles by employing the incompressible Stokes equation. They found that the sintering force can be evaluated from the neck growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Model of the initial stage of sintering. (a) Interaction of two particles12) , (b) A particle surrounded by eight neighbors13) .…”
mentioning
confidence: 99%
“…(a) Intermediate stage, (b) Final stage11) . Properties obtained by X-ray microtomography13) . (a) Relative density, (b) Specific surface area, (c) Average of curvature.…”
mentioning
confidence: 99%
See 1 more Smart Citation